Three-dimensional graphene with double atomic defects as well as preparation method and application of three-dimensional graphene
By introducing dual atomic defects into three-dimensional graphene, a controllable defect network is formed, which solves the problems of structural stability and cycle life of graphene in potassium ion capacitors, and improves high energy density and power density.
Patent Information
- Application Number
- CN202411885784.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
AI Technical Summary
When existing graphene materials store large radius potassium ions in potassium ion capacitors, they have poor structural stability and short cycle life, and traditional defect control methods have problems of structural stability and uneven distribution of defects.
Dual atomic defect guidance technology is adopted, and redox defects and structural defects are introduced through chemical vapor deposition method and low-temperature plasma technology to form a highly controllable defect network.
It significantly improves the energy density and power density of three-dimensional graphene, enhances structural stability and cycle life, and is suitable for high-performance energy storage devices such as potassium ion hybrid capacitors.
Smart Images

Figure CN119873807A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterials, and in particular relates to a three-dimensional graphene with double atomic-level defects and a preparation method and application thereof. Background Art
[0002] Graphene has attracted much attention in electrochemical energy storage devices (such as supercapacitors and batteries) due to its excellent properties such as high conductivity, high specific surface area, and high mechanical strength. By introducing the graphene structure, the conductivity of the electrode material can be effectively improved, the ion storage capacity can be enhanced, and thus the power density and energy density of the device can be improved. However, the electrochemical performance of graphene materials in practical applications still has some shortcomings, such as its low ability to store large-radius ions (such as potassium ions), and the structure is prone to change during the cycle, resulting in capacity decay. Therefore, how to further improve the electrochemical performance of graphene materials has become a current research hotspot.
[0003] Compared with lithium-ion capacitors, potassium-ion capacitors (KICs) have attracted much attention due to their low cost, abundant potassium resources, and high energy density, especially in the field of low-cost and large-scale energy storage. However, the radius of potassium ions is Large, easily causing volume expansion and structural collapse in the material, which poses a challenge to the structural stability and cycle life of the electrode material. In addition, due to the slow diffusion rate of potassium ions, it is difficult for traditional electrode materials to achieve efficient ion conduction, limiting the charge and discharge rate of potassium ion capacitors. Therefore, designing new electrode materials with high conductivity and excellent ion storage performance, especially graphene-based electrode materials, has become the key to solving the bottleneck problem of potassium ion capacitors.
[0004] In the preparation process of graphene materials, defects are generally considered to be inevitable, and these defects will significantly affect the electrochemical properties of graphene. In recent years, studies have shown that reasonable defect introduction and regulation techniques can change the electronic structure and surface properties of graphene, help improve the conductivity, specific surface area, active site distribution, etc. of the material, thereby improving its electrochemical performance. For example, doping with non-metallic elements (such as nitrogen, sulfur, etc.) or introducing microcrack structures have been shown to significantly improve the electrochemical activity of graphene. However, while these traditional defect regulation methods improve material performance, they often face problems such as poor structural stability and uneven defect distribution. Therefore, there is an urgent need for a new defect regulation technology that regulates the electrochemical properties of three-dimensional graphene by introducing dual atomic-level defects, making it suitable for application in potassium ion hybrid capacitors. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing three-dimensional graphene with double atomic-level defects.
[0006] Another object of the present invention is to provide three-dimensional graphene with double atomic-level defects obtained by the above preparation method.
[0007] Another object of the present invention is to provide applications of the above-mentioned three-dimensional graphene with double atomic defects.
[0008] The object of the present invention is achieved by the following technical solution: A method for preparing three-dimensional graphene with double atomic defects, comprising the following steps:
[0009] (1) Preparation of three-dimensional graphene material precursors
[0010] The biomass is placed as a raw material in a vacuum environment, and then pre-treated and carbonized in an inert atmosphere to obtain a three-dimensional graphene material precursor;
[0011] (2) Preparation of three-dimensional graphene materials
[0012] The three-dimensional graphene material precursor obtained in step (1) is placed in a vacuum environment, and treated by chemical vapor deposition (CVD) in a mixed gas of styrene and chlorine; then the three-dimensional graphene prepared by the chemical vapor deposition method is placed in a low-temperature plasma environment for further treatment to obtain a three-dimensional graphene sample;
[0013] (3) Preparation of dual-defect three-dimensional graphene materials
[0014] The three-dimensional graphene sample obtained in step (2) is placed in the middle position of a CVD reaction chamber; liquid diethylphosphamide is added to an evaporator of the CVD system, an inert gas is introduced, the temperature of the reaction chamber is gradually increased, the system pressure is adjusted, and a reaction is performed to obtain phosphorus-nitrogen co-doped three-dimensional graphene; and then a controllable laser system is used to perform laser irradiation on the phosphorus-nitrogen co-doped three-dimensional graphene to obtain a double-defect three-dimensional graphene material.
[0015] The biomass described in step (1) is preferably plant biomass; more preferably, it is grass biomass; and most preferably, it is bamboo fiber or natural reed.
[0016] The vacuum environment described in step (1) is preferably a vacuum quartz tube.
[0017] The pressure of the vacuum environment is 5-20 mTorr, preferably 10 mTorr.
[0018] The inert atmosphere in step (1) is preferably argon.
[0019] The flow rate of the inert atmosphere is preferably 40-80 sccm, and more preferably 60 sccm.
[0020] The temperature of the pretreatment carbonization in step (1) is 400-800°C, preferably 600°C.
[0021] The pretreatment carbonization time in step (1) is preferably 0.5 to 4 hours, more preferably 2 hours.
[0022] The vacuum environment described in step (2) is preferably a vacuum quartz tube.
[0023] The pressure of the vacuum environment is 5-20 mTorr, preferably 10 mTorr.
[0024] The styrene described in step (2) enters a heated gasifier through a gas conveying device at room temperature, and the temperature of the gasifier is maintained at 80°C.
[0025] The styrene described in step (2) uses argon as a carrier gas to carry gaseous styrene into the CVD reaction system.
[0026] The chlorine gas described in step (2) is directly supplied through a high-purity gas cylinder.
[0027] The flow ratio of the styrene to the chlorine is preferably 0.5-4:1, and more preferably 2:1.
[0028] The flow rate of styrene is preferably 50-100 sccm, and more preferably 80 sccm.
[0029] The flow rate of the chlorine gas is preferably 20-60 sccm, and more preferably 40 sccm.
[0030] The heating rate of the chemical vapor deposition process in step (2) is preferably 0.1 to 20 °C min -1 More preferably, 1 to 10 °C min -1 ; The most preferred temperature is 5℃min -1 .
[0031] The temperature of the chemical vapor deposition treatment in step (2) is preferably 100-1200°C; more preferably 400-1000°C; most preferably 900°C.
[0032] The time for the chemical vapor deposition treatment in step (2) is preferably 0.1 to 9 hours; more preferably 1 to 6 hours; and most preferably 3 hours.
[0033] The low-temperature plasma described in step (2) is preferably prepared by a low-temperature plasma generating device, which includes a vacuum chamber, a gas supply system, a plasma excitation source, an electrode system and a cooling system.
[0034] The preparation conditions of the low temperature plasma are preferably as follows: the chamber pressure is 10 -2 ~10 -6 Torr, the ratio of hydrogen (H2) to nitrogen (N2) is 1:3 to 1:5, the total gas flow rate is 50 to 200 sccm, the excitation radio frequency is 100 to 300 W, and the temperature range is 50 to 500 ° C; more preferably, the chamber pressure is 10 -4 Torr, the ratio of hydrogen (H2) to nitrogen (N2) is 1:4, the total gas flow rate is 100 sccm, the excitation radio frequency is 200 W, and the temperature range is 300 °C.
[0035] The inert atmosphere is preferably argon.
[0036] The temperature of the further treatment in step (2) is preferably 50-500°C; more preferably 300°C.
[0037] The time for the further treatment in step (2) is preferably 0.1 to 2 h; more preferably 1 h.
[0038] The amount of liquid diethylphosphamide used in step (3) is preferably calculated based on 5 to 20 mL of liquid diethylphosphamide per 100 mg of three-dimensional graphene sample; more preferably, 10 mL of liquid diethylphosphamide per 100 mg of three-dimensional graphene sample.
[0039] The temperature of the evaporator in step (3) is 40-100°C, preferably 70°C.
[0040] The inert gas described in step (3) is preferably argon.
[0041] The flow rate of the inert gas in step (3) is 0 to 50 sccm, excluding the endpoint value 0; preferably 20 sccm.
[0042] The temperature of the reaction chamber in step (3) is 200-1000°C, preferably 600°C.
[0043] The system pressure in step (3) is 10 -1 ~10 -4 Torr; preferably 10 -2 Torr.
[0044] The reaction time in step (3) is 0.5 to 4 hours, preferably 2 hours.
[0045] The power density of the laser irradiation in step (3) is 1 to 8 W / cm 2 ; preferably 5W / cm 2 .
[0046] The laser irradiation time in step (3) is 5 to 20 minutes, preferably 10 minutes.
[0047] A three-dimensional graphene regulated by dual atomic-level defects is obtained by the above preparation method. It has higher energy density and power density and is particularly suitable for high-performance energy storage devices such as potassium ion hybrid capacitors.
[0048] The application of the above-mentioned three-dimensional graphene with double atomic-level defects in the field of electrochemical energy storage technology is particularly suitable for the preparation of potassium ion hybrid capacitors, lithium ion batteries, sodium ion batteries or supercapacitors.
[0049] A potassium ion hybrid capacitor comprises a positive electrode, a negative electrode, a separator and an electrolyte; the material of the negative electrode is the above-mentioned three-dimensional graphene with double atomic-level defects.
[0050] The material of the positive electrode is the three-dimensional graphene with double atomic defects mentioned above which is completely activated by KOH solution.
[0051] The specific preparation steps of the material thoroughly activated by KOH solution are preferably as follows: fully mixing the three-dimensional graphene with double atomic defects and potassium hydroxide solution, wherein the three-dimensional graphene with double atomic defects and potassium hydroxide are mixed in a mass ratio of 1:3; heating the mixture to 800°C in an inert atmosphere at a heating rate of 5°C / min and maintaining it for 2 hours; washing the activated product with hydrochloric acid to remove excess activator, then repeatedly rinsing with deionized water, and then drying to obtain the three-dimensional graphene with double atomic defects activated by KOH.
[0052] The electrolyte is a KFSI solution with diethyl carbonate and ethylene carbonate (DEC / EC, 1:1, volume ratio) as solvent, and the concentration of KFSI is 1M.
[0053] The diaphragm is glass microfiber, preferably Whatman GF / F glass microfiber.
[0054] The positive electrode and the negative electrode can be cut into suitable sizes before assembly, preferably a circle with a diameter of 14 mm.
[0055] The potassium ion hybrid capacitor is assembled in a glove box filled with argon, preferably with an oxygen concentration of <0.5ppm and a water concentration of <0.5ppm.
[0056] The potassium ion hybrid capacitor device has excellent rapid charging and discharging performance and is suitable for application in the field of electrochemical energy storage technology.
[0057] Compared with the prior art, the present invention has the following advantages and effects:
[0058] (1) The present invention provides a "dual atomic-level defect-guiding technology" that creates a highly controllable defect network in three-dimensional graphene materials by simultaneously introducing redox defects and structural defects. This technology can not only achieve defect diversity, but also precisely control the distribution and density of defects, so that the defects are more evenly distributed on the material surface, thereby improving the structural stability of the material.
[0059] (2) The novel phosphamide compound (diethylphosphamide, (C2H5O)2P(O)NH2) provided by the present invention is used as a phosphorus and nitrogen co-doping source, and a one-step chemical vapor deposition (CVD) method is combined with low-temperature plasma technology to achieve efficient and uniform doping regulation. The process is simple and easy, avoiding the high energy consumption and pollution problems of traditional multi-step chemical treatment.
[0060] (3) A three-dimensional graphene nanomaterial with dual atomic-level defect guidance and regulation provided by the present invention is used as a negative electrode to obtain a potassium ion capacitor with high capacity, high rate and long life. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The scanning electron microscope image and transmission electron microscope image of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterial prepared in Example 1; wherein (a) is a scanning electron microscope image of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterial when the scale is 2 μm; (b) is a transmission electron microscope image of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterial when the scale is 50 nm.
[0062] Figure 2 Figure 1 shows the Raman spectrum characterization test results of the phosphorus and nitrogen co-doped three-dimensional graphene nanomaterial prepared in Example 1 (a) and the X-ray photoelectron spectrum (b).
[0063] Figure 3 The nitrogen adsorption-desorption curves of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials prepared in Example 1 are as follows; wherein (a) is a nitrogen adsorption-desorption curve of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials; and (b) is a nitrogen adsorption-desorption curve of the three-dimensional graphene nanomaterials.
[0064] Figure 4 The electron paramagnetic resonance spectra of the three-dimensional graphene nanomaterial prepared in Example 1 and the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterial.
[0065] Figure 5 This is a diagram of the element content of the phosphorus and nitrogen co-doped three-dimensional graphene nanomaterial prepared in Example 1.
[0066] Figure 6 This is the rate performance diagram of potassium ion hybrid capacitor devices.
[0067] Figure 7 This is a diagram of the long cycle life of the potassium ion hybrid capacitor device in Example 1. DETAILED DESCRIPTION
[0068] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0069] Example 1
[0070] 1. A method for preparing three-dimensional graphene nanomaterials regulated by dual atomic-level defects:
[0071] (1) Preparation of three-dimensional graphene material precursors
[0072] Bamboo fiber was taken as raw material and placed in a vacuum quartz tube, and then pre-treated and carbonized in an argon atmosphere at 600° C. for 2 hours, wherein the flow rate of argon was 60 sccm.
[0073] (2) Preparation of three-dimensional graphene materials
[0074] The three-dimensional graphene material precursor obtained in step (1) is placed in a vacuum quartz tube, styrene is introduced into the CVD reaction system at a flow rate of 80 sccm using argon as a carrier gas (the volume concentration of styrene in argon is usually set at 50%), and chlorine is introduced into the CVD reaction system at a flow rate of 40 sccm. The CVD reaction system is heated at 5°C min -1 The temperature is raised at a heating rate of 900° C. In a mixed gas of styrene and chlorine, the three-dimensional graphene material precursor is subjected to CVD treatment at 900° C. for 3 hours.
[0075] The low-temperature plasma was prepared using a plasma enhanced chemical vapor deposition system, where the chamber pressure was 10 -4 Torr, the ratio of hydrogen (H2) to nitrogen (N2) is 1:4, the total gas flow rate is 100 sccm, the excitation radio frequency is 200 W, and the temperature range is 300 °C.
[0076] The three-dimensional graphene prepared by CVD was placed in a low-temperature plasma environment and treated at 300°C for 1 hour to obtain a three-dimensional graphene sample.
[0077] (3) Preparation of dual-defect three-dimensional graphene materials
[0078] 100 mg of the three-dimensional graphene sample obtained in step (2) is placed in the middle position of the CVD reaction chamber; 10 mL of liquid diethylphosphamide (referring to dichloro N, N-diethylphosphamide, CAS number 1069-08-5) is added to the evaporator of the CVD system, and the temperature of the evaporator is set to 70°C; argon gas is introduced, and the flow rate is controlled to 20 sccm; the temperature of the reaction chamber is gradually increased to 600°C, and the system pressure is adjusted to 10-2 Torr, and the reaction time is 2 hours; a controllable laser system is used to irradiate the phosphorus and nitrogen co-doped three-dimensional graphene with a laser, and the laser power density is controlled at 5 W / cm 2 , the irradiation time is 10 min, and a three-dimensional graphene material with double defects is obtained.
[0079] 2. Detection
[0080] (1) Structural composition detection
[0081] The prepared double-defect three-dimensional graphene nanomaterials were tested by field emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results are as follows: Figure 1 As shown, these nanosheets can interconnect and form a 3D carbon framework with randomly distributed pores ( Figure 1 (a)); TEM images clearly show that the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterial exhibits a nanosheet structure similar to a silk veil, while its surface also shows an uneven wrinkle morphology consistent with the SEM results ( Figure 1 (b) in the figure.
[0082] The prepared double-defect three-dimensional graphene nanomaterials were characterized by Raman spectroscopy and high-resolution XPS. Figure 2 As shown: (a) shows the ratio of the two peak intensities of phosphorus and nitrogen co-doped three-dimensional graphene nanomaterials I D / I G It reached 1.29, indicating that the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials have very rich defects in the edges and planes of graphene sheets; (b) shows that the C1s peak is fitted into five peaks, corresponding to the C=C bond, CO bond, CN bond, CP bond and C=C bond that occupy the main components.
[0083] The prepared double-defect three-dimensional graphene nanomaterials were characterized by N2 adsorption-desorption analysis. Figure 3 As shown. Figure 3 It can be seen that the specific surface area of the three-dimensional graphene nanomaterial prepared in step (2) is 486.72 m 2 g -1 The specific surface area of the dual-defect three-dimensional graphene nanomaterial prepared in step (3) is 542.39 m 2 g-1 , indicating that the specific surface area of three-dimensional graphene nanomaterials increased after phosphorus-nitrogen co-doping and laser irradiation treatment.
[0084] The electron paramagnetic resonance spectroscopy of the double-defect three-dimensional graphene nanomaterials was characterized. Figure 4 Shown: Indicates that nitrogen atoms, phosphorus atoms and defects have been successfully introduced into the surface of three-dimensional graphene nanomaterials.
[0085] The element content of the double-defect three-dimensional graphene nanomaterials was characterized. Figure 5 As shown: the contents of nitrogen atoms and phosphorus atoms are 8.59at% and 3.57at%, respectively.
[0086] (2) Performance testing
[0087] Activation of dual-defect three-dimensional graphene nanomaterials (NP-3DPG): NP-3DPG and potassium hydroxide solution are fully mixed to obtain a mixture, in which NP-3DPG and activator potassium hydroxide are mixed in a mass ratio of 1:3. The mixture is placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under an argon protective atmosphere and maintained for 2 hours. The activated product is washed with hydrochloric acid to remove excess activator, and then rinsed repeatedly with deionized water. Finally, the product is placed in an oven at 60°C and dried overnight to obtain activated NP-3DPG, which is the positive electrode material ANP-3DPG.
[0088] Assembly of potassium ion hybrid capacitors (PIHCs) devices: Potassium ion hybrid capacitors were constructed using NP-3DPG as the negative electrode material and ANP-3DPG activated by KOH as the positive electrode material. To optimize the performance of the device, the mass ratio of the negative electrode to the positive electrode active material was set to 1:3.
[0089] Before assembling the complete ANP-3DPG / / NP-3DPG potassium ion hybrid capacitor, the negative electrode NP-3DPG and the positive electrode ANP-3DPG need to be pretreated. Under half-cell conditions, at a current density of 0.2A -1 The activation treatment was carried out for 5 cycles at a current density of , and finally the negative electrode material was potassiumized to a state of 0.01V.
[0090] The electrolyte used is 1.0M KFSI (potassium fluorosulfonyl imide) dissolved in a mixed solvent of EC:DEC (1:1 volume ratio), and the diaphragm is Whatman brand GF / F glass fiber membrane. The assembly and disassembly of the potassium ion hybrid capacitor are carried out in a glove box filled with argon (the moisture content and oxygen content in the glove box should be kept within <0.1ppm) to ensure that the device is not affected by external air and moisture. The constant current charge and discharge test method is used to study the energy storage performance of the prepared potassium ion hybrid capacitor device. The constant current charge and discharge test of the potassium ion capacitor is completed at room temperature and on the Shanghai Huachen CHI 760D electrochemical workstation. The test voltage window is 0-4.0V. The results are as follows Figure 6 As shown. Figure 6 It can be seen that the capacity of the potassium ion capacitor prepared above ranges from 0.05Ag -1 135.6mAh g -1 Change to 10Ag -1 25.83mAh g -1 , indicating that it has good rate capacity.
[0091] The long-term cycle test of the potassium ion capacitor device was carried out, and the results are as follows Figure 7 As shown, the potassium ion capacitor device is -1 and 2.0A g -1 After 20,000 consecutive charge and discharge cycles at a current density of , the capacity retention rates were 98.2% and 96.5%, respectively, indicating that the potassium ion capacitor device has good cycle stability.
[0092] Embodiment 2-5
[0093] The preparation method of Example 2-5 is the same as that of Example 1, except for the temperature used for the precursor pretreatment in step (1). The specific temperature control in the preparation method of Example 2-5 is shown in Table 1.
[0094] Table 1 Temperature control of precursor pretreatment
[0095]
[0096] Embodiment 6-9
[0097] The preparation methods of Examples 6-9 are the same as those of Example 1, except for the time used for the precursor pretreatment in step (1). The specific temperature control in the preparation methods of Examples 6-9 is shown in Table 2.
[0098] Table 2 Time regulation of precursor pretreatment
[0099]
[0100] Examples 10-13
[0101] The preparation methods of Examples 10-13 are the same as those of Example 1, except that in step (2), the flow ratio of styrene to chlorine during the growth of the three-dimensional graphene material is 100 sccm. The specific flow ratio of styrene to chlorine during the growth of the three-dimensional graphene material in the preparation methods of Examples 10-13 is shown in Table 3.
[0102] Table 3 Flow ratio control of styrene and chlorine
[0103]
[0104]
[0105] Examples 14-17
[0106] The preparation methods of Examples 14-17 are the same as those of Example 1, except for the temperature used for the CVD treatment in step (2). The specific temperature control in the preparation methods of Examples 14-17 is shown in Table 4.
[0107] Table 4 Temperature control of CVD process
[0108]
[0109] Examples 15-18
[0110] The preparation methods of Examples 15-18 are the same as those of Example 1, except for the time used for the CVD treatment in step (2). The specific time control in the preparation methods of Examples 15-18 is shown in Table 5.
[0111] Table 5 Time control of CVD treatment
[0112]
[0113] Examples 19-22
[0114] The preparation methods of Examples 19-22 are the same as those of Example 1, except for the temperature used for the plasma CVD treatment in step (2). The specific temperature control in the preparation methods of Examples 19-22 is shown in Table 6.
[0115] Table 6 Temperature control of plasma CVD treatment
[0116]
[0117]
[0118] Examples 23-26
[0119] The preparation methods of Examples 23-26 are the same as those of Example 1, except that the volume of diethylphosphonamide used in step (3) is different. The specific volume control in the preparation methods of Examples 23-26 is shown in Table 7.
[0120] Table 7 Volume Control of Diethylphosphonamide
[0121]
[0122] Examples 27-30
[0123] The preparation methods of Examples 27-30 are the same as those of Example 1, except for the power density of the laser in step (3). The specific power density control in the preparation methods of Examples 27-30 is shown in Table 8.
[0124] Table 8 Laser power density control
[0125]
[0126] It can be seen that the potassium ion capacitor device of the present invention has the characteristics of large capacity, high rate, long life, and also has the advantages of high energy density, and has great application prospects in the field of electrochemical energy storage technology.
[0127] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing three-dimensional graphene with double atomic defects, characterized in that The steps include: (1) Preparation of three-dimensional graphene material precursors The biomass is placed in a vacuum environment as a raw material, and then pre-treated and carbonized in an inert atmosphere to obtain a three-dimensional graphene material precursor; (2) Preparation of three-dimensional graphene materials The three-dimensional graphene material precursor obtained in step (1) is placed in a vacuum environment, and treated by chemical vapor deposition (CVD) in a mixture of styrene and chlorine; then the three-dimensional graphene prepared by chemical vapor deposition is placed in a low-temperature plasma environment for further treatment to obtain a three-dimensional graphene sample; (3) Preparation of dual-defect three-dimensional graphene materials The three-dimensional graphene sample obtained in step (2) is placed in the middle position of a CVD reaction chamber; liquid diethylphosphamide is added to an evaporator of the CVD system, an inert gas is introduced, the temperature of the reaction chamber is gradually increased, the system pressure is adjusted, and a reaction is performed to obtain phosphorus-nitrogen co-doped three-dimensional graphene; and then a controllable laser system is used to perform laser irradiation on the phosphorus-nitrogen co-doped three-dimensional graphene to obtain a double-defect three-dimensional graphene material.
2. The method for preparing three-dimensional graphene with double atomic defects according to claim 1, characterized in that: The temperature of the pretreatment carbonization in step (1) is 400-800°C; The pretreatment carbonization time in step (1) is 0.5 to 4 hours; The flow rate of styrene in step (2) is 50 to 100 sccm; The flow rate of the chlorine gas in step (2) is 20 to 60 sccm; The flow ratio of the styrene and the chlorine in step (2) is 0.5 to 4:1; The temperature of the chemical vapor deposition process in step (2) is 100 to 1200° C. The chemical vapor deposition treatment time in step (2) is 0.1 to 9 hours; The temperature of the further treatment in step (2) is 50 to 500° C.; The further treatment time described in step (2) is 0.1 to 2 hours; The temperature of the reaction chamber in step (3) is 200-1000° C.; The system pressure described in step (3) is 10- 1 ~10- 4 Torr; The reaction time in step (3) is 0.5 to 4 hours; The amount of liquid diethylphosphonamide used in step (3) is calculated based on 5 to 20 mL of liquid diethylphosphonamide per 100 mg of three-dimensional graphene sample; The power density of the laser irradiation in step (3) is 1 to 8 W / cm 2 ; The laser irradiation time in step (3) is 5 to 20 minutes.
3. The method for preparing three-dimensional graphene with double atomic defects according to claim 2, characterized in that: The temperature of the pretreatment carbonization in step (1) is 600°C; The pretreatment carbonization time in step (1) is 2 hours; The temperature of the chemical vapor deposition process in step (2) is 400-1000° C.; The chemical vapor deposition treatment time in step (2) is 1 to 6 hours; The temperature of the further treatment described in step (2) is 300°C; The further treatment time described in step (2) is 1 h; The temperature of the reaction chamber in step (3) is 600° C. The system pressure described in step (3) is 10- 2 Torr; The reaction time in step (3) is 2 hours; The amount of the liquid diethylphosphonamide described in step (3) is calculated based on 10 mL of liquid diethylphosphonamide per 100 mg of three-dimensional graphene sample; The power density of the laser irradiation in step (3) is 5 W / cm 2 ; The laser irradiation time in step (3) is 10 minutes.
4. The method for preparing three-dimensional graphene with double atomic defects according to claim 1, characterized in that: The biomass described in step (1) is plant biomass; The vacuum environment described in step (1) is a vacuum quartz tube; The inert atmosphere described in step (1) is argon; The vacuum environment described in step (2) is a vacuum quartz tube; The styrene described in step (2) uses argon as a carrier gas; The inert gas described in step (3) is argon; The inert gas described in step (3) is argon.
5. The method for preparing three-dimensional graphene with double atomic defects according to claim 1, characterized in that: The pressure of the vacuum environment described in step (1) is 5 to 20 mTorr; The flow rate of the inert atmosphere in step (1) is 40 to 80 sccm; The pressure of the vacuum environment described in step (2) is 5 to 20 mTorr; The flow rate of the inert gas described in step (3) is 0 to 50 sccm, excluding the endpoint value 0.
6. The method for preparing three-dimensional graphene with double atomic defects according to claim 1, characterized in that: The heating rate of the chemical vapor deposition process in step (2) is 0.1-20°C min -1 ; The preparation conditions of the low temperature plasma described in step (2) are as follows: the chamber pressure is 10- 2 ~10- 6 Torr, the ratio of hydrogen to nitrogen is 1:3 to 1:5, the total gas flow rate is 50 to 200 sccm, the excitation radio frequency is 100 to 300 W, and the temperature range is 50 to 500 ° C; The temperature of the evaporator described in step (3) is 40-100°C.
7. A three-dimensional graphene controlled by dual atomic-level defect guidance, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 6.
8. A potassium ion hybrid capacitor, characterized in that: It comprises a positive electrode, a negative electrode, a separator and an electrolyte; the material of the negative electrode is the three-dimensional graphene with double atomic defects as described in claim 7; the material of the positive electrode is the three-dimensional graphene with double atomic defects as described in claim 7 which is completely activated by a KOH solution.
9. The potassium ion hybrid capacitor according to claim 8, characterized in that: The electrolyte is a KFSI solution using a solution obtained by mixing diethyl carbonate and ethylene carbonate in a volume ratio of 1:1 as a solvent, and the concentration of KFSI is 1M; The diaphragm is glass microfiber.
10. Application of the three-dimensional graphene with double atomic-level defects as claimed in claim 7 and the potassium ion hybrid capacitor device as claimed in claim 8 or 9 in the field of electrochemical energy storage technology.
Citation Information
Patent Citations
Method for preparing nitrogen and phosphorus codoped porous graphene material
CN103570011A
Preparation method of nitrogen, sulfur, and phosphor doped graphene sheet
CN104828811A
Method for directly preparing co-doping three-dimensional graphene electrode material through biomass carbon sources
CN105314629A
Method for preparing doped graphene or graphene-like compound
CN105810956A
A preparation method of multi-isoatom doped three-dimensional graphene
CN109004186A